Growth and Evolution of Secondary Volcanic Atmospheres: 2. The Importance of Kinetics. Issue 3 (16th March 2023) - Liggins, Philippa; Jordan, Sean; Rimmer, Paul B.; Shorttle, Oliver
Abstract: Volcanism is a major and long‐term source of volatile elements such as C and H to Earth's atmosphere, likely has been to Venus's atmosphere, and may be for exoplanets. Models simulating volcanic growth of atmospheres often make one of two assumptions: either that atmospheric speciation is set by the high‐temperature equilibrium of volcanism or that volcanic gases thermochemically reequilibrate to the new, lower, temperature of the surface environment. In the latter case, it has been suggested that volcanic atmospheres may create biosignature false positives. Here, we test the assumptions underlying such inferences by performing chemical kinetic calculations to estimate the relaxation timescale of volcanically derived atmospheres to thermochemical equilibrium, in a simple 0D atmosphere neglecting photochemistry and reaction catalysis. We demonstrate that for planets with volcanic atmospheres, thermochemical equilibrium over geological timescales can only be assumed if the atmospheric temperature is above ∼700 K. Slow chemical kinetics at lower temperatures inhibit the relaxation of redox‐sensitive species to low‐temperature thermochemical equilibrium, precluding the production of two independent biosignatures through thermochemistry alone: 1. ammonia and 2. the cooccurrence of CO2 and CH4 in an atmosphere in the absence of CO. This supports the use of both biosignatures for detecting life. Quenched at the high temperature of their degassing, volcanic gases also have speciations characteristic of those produced from a more oxidized mantle, if interpreted as being at thermochemical equilibrium. This therefore complicates linking atmospheres to the interiors of rocky exoplanets, even when their atmospheres are purely volcanic in origin. Plain Language Summary: Rocky planets can build up atmospheres over time through the release of volcanic gases. Simulations of this process usually assume that the chemistry of these atmospheres will either be controlled by the temperature the gases were erupted at or by the current temperature of the atmosphere. We test these assumptions by calculating the time it will take for the chemistry of an atmosphere built of volcanic gases to change from being controlled by the temperature of eruption to a chemistry reflecting the current atmospheric temperature. We find that without additional processes (e.g., atmospheric photochemistry or reaction catalysis) speeding up the rates of reactions, atmospheres with temperatures below 700 K will always have chemistries which reflect their emission temperature, rather than the current atmospheric temperature. Cool planets with volcanically derived atmospheres should therefore not be modeled while assuming the atmospheric chemistry is controlled by the current temperature. These results also support the use of both ammonia and the combined presence of carbon dioxide and methane (in the absence of carbon monoxide) as biosignatures for detecting the presence of life on other planets. Key Points: Thermochemical equilibrium cannot be assumed for volcanically derived atmospheres with temperatures <700 K Quenching of volcanically derived atmospheres will limit linking of their chemistry to underlying mantle f O2 Warm to cool volcanic atmospheres produce CO2 and CH4, but with CO present, preventing them being mistaken for positive biosignatures